Utilizing group-based models to identify adverse event patterns after an intervention - Wang, Wei; Abbaspour, Sara; Blumenthal, Kimberly G.; Hashimoto, Dean M.; Robbins, Gregory K.; Klerman, Elizabeth B. (Frontiers in Medicine, 2025)
BackgroundStandard adverse event (AE) monitoring only records whether events occur after the intervention, and not whether these events vary over time.ObjectiveTo test whether there were statistically distinct time-varying trajectories of AE (e.g., “side effects”) after an intervention and identify characteristics of individuals associated with these patterns.DesignGroup-based trajectory models applied to an observational study of individuals who received one or two doses of a mRNA COVID-19 vaccine (i.e., the intervention).Participants50,484 healthcare personnel who received their vaccinations within the Mass General Brigham (MGB) healthcare system.InterventionsVaccination.Main measuresAllergic and non-allergic AE for 1–3 days after each of two COVID-19 vaccinations.Key resultsTrajectories models identified distinct groups with different trajectories after intervention: two groups after the first vaccination and five groups after the second vaccination. These groups differed by demographics, age, prior prescription for epinephrine auto-injectors, prior COVID-19 history, time-of-day of vaccination, and vaccine manufacturer.ConclusionSeveral different time-based trajectories after the intervention (e.g., first two COVID-19 vaccinations) were noted; individuals in these groups varied by demographic and clinical criteria. These time-based methods may be able to identify groups at higher risk of future adverse reactions, provide a basis for future studies of the physiology underlying these risk differentials, and improve counseling surrounding interventions associated with AEs. We suggest that trajectory-based methods be added to post-intervention surveillance.